Approach to nigericin derivatives and their therapeutic potential - Sahu, Amit Kumar; Said, Madhukar S.; Hingamire, Tejashri; Gaur, Megha; Khan, Abujunaid; Shanmugam, Dhanasekaran; Barvkar, Vitthal T.; Dharne, Mahesh S.; Bharde, Atul A.; Dastager, Syed G. (RSC Advances, 2020)
A new nigericin analogue that has been chemically modified was synthesized through a fluorination process from the parent nigericin, produced from a novel Streptomyces strain DASNCL-29. Fermentation strategies were designed for the optimised production of nigericin molecule and subjected for purification and structural analysis. The fermentation process resulted in the highest yield of nigericin (33% (w/w)). Initially, nigericin produced from the strain DASNCL-29 demonstrated polymorphism in its crystal structure, i.e., monoclinic and orthorhombic crystal lattices when crystallised with methanol and hexane, respectively. Furthermore, nigericin produced has been subjected to chemical modification by fluorination to enhance its efficacy. Two fluorinated analogues revealed that they possess a very potent antibacterial activity against Gram positive and Gram negative bacteria. To date, the nigericin molecule has not been reported for any reaction against Gram-negative bacteria, which are increasingly becoming resistant to antibiotics. For the first time, fluorinated analogues of nigericin have shown promising activity. In vitro cytotoxicity analysis of fluorinated analogues demonstrated tenfold lesser toxicity than the parent nigericin. This is the first type of study where the fluorinated analogues of nigericin showed very encouraging activity against Gram-negative organisms; moreover, they can be used as a candidate for treating many serious infections.

Total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate and its antimicrobial potentials - Said, Madhukar S.; Udavant, Rohini; Sahu, Amit Kumar; Khan, Abujunaid; Nayak, Rashmi; Dastager, Syed G.; Kumar, Pradeep; Gajbhiye, Jayant (Natural Product Research, 2020)
The first total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate (butenolide cinnamate) was achieved using commercially available starting material. The synthesized compound was found to have promising antibacterial activity against Gram-negative strainsEscherichia coli(ATCC 8739),Salmonella typhimurium(ATCC 23564) andPseudomonas aeruginosa(ATCC 19154) with a minimum inhibitory concentration of 2.0 mu g/mL, 1.0 mu g/mL and 2.0 mu g/mL, respectively. Notably, the compound was more potent against Gram-negative test strains than the Gram-positive test strains.
Keywords: antibacterial activity; butenolide cinnamate; Total synthesis

Enceleamycins A-C, furo-naphthoquinones from amycolatopsis sp. MCC0218: isolation, structure elucidation, and antimicrobial activity - Khan, Abujunaid; Said, Madhukar S.; Borade, Balasaheb R.; Gonnade, Rajesh; Barvkar, Vitthal; Kontham, Ravindar; Dastager, Syed G. (Journal of Natural Products, 2022)
Three novel furo-naphthoquinones, enceleamycins A-C (1-3), and a new N-hydroxypyrazinone acid (4) were identified from the strain Amycolatopsis sp. MCC 0218, isolated from a soil sample collected from the Western Ghats of India. Their chemical structure and absolute and relative configurations were established by 1D and 2D NMR spectroscopy, single-crystal X-ray crystallography, and high-resolution mass spectrometry. Compounds 1 and 3 were active against methicillin-susceptible and -resistant Staphylococcus aureus with MIC values of 2-16 mu g/mL.

In vitro anticancer evaluation of enceleamycin A and its underlying - Khan, Abujunaid; Pradeep, S.; Dastager, Syed G. (RSC Advances, 2023)
It has become more crucial than ever to find novel anticancer compounds due to the rise in cancer mortality and resistance to the present chemotherapeutic drugs. Naphthoquinones are regarded as privileged structures for their ability to inhibit various cancers. The current study examined three novel furo-naphthoquinones (Enceleamycins A-C) previously isolated from Amycolatopsis sp. MCC 0218 for their anticancer potential. Enceleamycin A demonstrated considerable cytotoxicity for triple-negative breast cancer (TNBC) MDA-MB-231 cells with an IC50 value of 1.25 mu g mL(-1) (3.78 mu M). It also showed the ability to inhibit MDA-MB-231 cell migration. Enceleamycin A raises intracellular ROS levels in TNBC cells, ultimately leading to apoptotic cell death, as demonstrated by Annexin V/PI staining. The molecular docking and simulation investigation revealed better binding affinity of Enceleamycin A with AKT2, which plays a vital role in breast cancer's invasiveness and chemo-resistance. Enceleamycin A inhibits the AKT2 enzyme in vitro with an IC50 value of 0.736 mu g mL(-1) (2.22 mu M), further validating the docking study. The in silico physicochemical and pharmacokinetics characteristics of Enceleamycin A demonstrated its drug-likeness. Intriguingly, Enceleamycin A is non-hemolytic in nature. Taken together, Enceleamycin A could be a candidate molecule for treating TNBC cells by targeting the AKT2 signaling pathway.
Keywords: Assay; cancer; Derivatives; Naphthoquinones; Plays

Boron- and oxygen-doped π-extended helical nanographene with circularly polarised thermally activated delayed fluorescence - Venugopal, Geethu; Kumar, Viksit; Jadhav, Ashok Badrinarayan; Dongre, Sangram D.; Khan, Abujunaid; Gonnade, Rajesh; Kumar, Jatish; Santhosh Babu, Sukumaran (Chemistry-A European Journal, 2024)
Helical nanographenes have garnered substantial attention owing to their finely adjustable optical and semiconducting properties. The strategic integration of both helicity and heteroatoms into the nanographene structure, facilitated by a boron-oxygen-based multiple resonance (MR) thermally activated delayed fluorescence (TADF), elevates its photophysical and chiroptical features. This signifies the introduction of an elegant category of helical nanographene that combines optical (TADF) and chiroptical (CPL) features. In this direction, we report the synthesis, optical, and chiroptical properties of boron, oxygen-doped pi-extended helical nanographene. The pi-extension induces distortion in the DOBNA-incorporated nanographene, endowing a pair of helicenes, (P)-B2NG, and (M)-B2NG exhibiting circularly polarized luminescence with glum of -2.3x10-3 and +2.5x10-3, respectively. B2NG exhibited MR-TADF with a lifetime below 5 mu s, and a reasonably high fluorescence quantum yield (50 %). Our molecular design enriches the optical and chiroptical properties of nanographenes and opens up new opportunities in multidisciplinary fields. B, O-doped pi-extended helical nanographene has been explored for its optical and chiroptical properties. The presence of helical and nanographene segments stabilize the helicity and imparts tunable optical properties. Helical nanographene display circularly polarized thermally activated delayed fluorescence. image
Keywords: circularly polarized luminescence; DOBNA; dual emission; nanographene; TADF

Integrated genomic and functional analysis of Streptomyces sp. UP1A-1 for bacterial wilt control and solanaceae yield increase - Kaari, Manigundan; Manikkam, Radhakrishnan; Joseph, Jerrine; Krishnan, Sakthivel; Annamalai, Kishore Kumar; Khan, Abujunaid; Rajput, Vinay; Dastager, Syed Gulam; Dharne, Mahesh S.; Umar, Md; Venugopal, Gopikrishnan; Alexander, Balamurugan (Gene Reports, 2024)
<em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Ralstonia solanacearum<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> is one of the most destructive soil-borne pathogen, causing bacterial wilt to the solanaceae vegetables. <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 isolated from healthy solanaceae rhizosphere soil, exhibited the lowest disease incidence and increased fruit yield of solanaceae vegetables. However, the genomic and functional properties of UP1A-1 are unclear. Therefore, we conducted the present study to elucidate the genomic characteristics of UP1A-1 by whole genome sequencing. The results indicate that the genome of <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 consists of 8,252,902 bp and contains 72.42 % G + C. We identified the genes that confer plant growth promoting (PGP) function, which include those involved in siderophore production, indole-3-acetic acid biosynthesis, phosphate solubilization, nitrogen metabolism, and potassium metabolism. We also identified several other genes, such as chitinase, peroxidase, superoxide dismutase, catalase, proline biosynthesis, and glucose dehydrogenase, which are believed to be involved in the control of wilt disease. These genes revealed that the strain UP1A-1 has physiologically adapted to varied environmental conditions and could potentially control both abiotic and biotic stresses.